(untitled) (Nigerian Journal of Health Sciences, 2023)
Background: Diabetes in pregnancy constitutes a high risk factor for increased maternal and perinatal morbidity and mortality. There is inadequate knowledge of the diabetic pregnancy and its impact on neonatal health in our environment, hence the need for more research. Objective: To describe the morbidity pattern among infants of diabetic mothers (IDMs). Materials and Methods: Hospital records of all neonates diagnosed as IDMs and admitted into the neonatal ward of a tertiary hospital in South-Western Nigeria over a 10-year period were reviewed. Relevant data were extracted and analyzed. Results: Twenty-four cases met inclusion criteria, with a slight male preponderance. Mean (standard deviation [SD]) gestational age was 38.1 (1.8) weeks while the mean (SD) birth weight was 3.9 (0.4) kg. Fifty-eight percent of the subjects were delivered by cesarean section. 12 (50%) babies were macrosomic while the most common morbidities among the subjects were hypoglycemia, neonatal jaundice, and birth asphyxia which were observed in 75%, 75%, and 33.3% of the study population, respectively. Less frequently observed conditions include prematurity, transient tachypnea of the newborn, neonatal sepsis, and birth injury. 2 (8.3%) babies presented with congenital malformation affecting the heart and central nervous system, respectively. There was only one case of mortality. Conclusion: IDMs are prone to macrosomia, hypoglycemia, neonatal jaundice, and birth asphyxia in our environment. Early antenatal screening of all pregnant women for diabetes mellitus is required and good glycemic control of diabetic pregnancies should be the ultimate goal in order to minimize neonatal complications.